Exploring Learning Experience in a Total Enterprise Simulation Based on Means-End Theory - SAI, Fuyume (International Journal of Management and Sustainability, 2017)
The primary purpose of this study was to obtain empirical evidence and provide a methodological alternative for helping understand how simulation serves to learning. Well-structured system design and unstructured learning implementation bring complexity to dealing with learning in total enterprise simulation, specially, how to investigate learning emanated from the simulation game’s structure and decision-making requirements has studied very few. Due to the multiple aspects of individual learning situation and the inevitable structural design differences in simulations, student authored reports were used as data source to analyze the connections of learning-performance based on means-ends theory and the model was constructed with the components, namely Attributes, Consequences, and Values. With limitations of research, the study provides practical evidence and student insight into logic and structure of the simulated firm experienced, as well as demonstrates the use of means-ends approach for research on the issue of simulation-based learning and performance.